The Influence of Career Development and Organizational Support on Employee Performance - Mohammad Alvito; Sadillah Zam Nastiar; Kartono - (Universitas KH. Abdul Chalim Mojokerto, 2025)
In an increasingly competitive era of globalization, career development and organizational support are important factors in improving employee performance. This study aims to analyze the effect of career development and organizational support on employee performance in manufacturing companies in Cirebon. A quantitative approach with an associative design was used in this study. The research sample consisted of 98 employees from a population of 4,000 employees of PT Arteria Daya Mulia, who were selected by a simple random sampling method. The results revealed that career development has a positive and significant influence on employee performance. Employees who have access to training, seminars, and promotion opportunities tend to have higher work motivation. In addition, organizational support also has a significant impact on improving employee performance. Support in the form of attention from superiors, a conducive work environment, and policies that encourage professional growth are proven to increase employee loyalty and productivity.